Prevalencia de Toxoplasmosis en Caninos Domésticos (canis familiaris) en el Barrio San Felipe-Latacunga. - Taipe Llerena, María Ángela (2018)
The purpose of this research work was to determine the prevalence of toxoplasmosis in domestic canines (canis familiaris) in the San Felipe neighborhood of the Latacunga city, through the indirect ELISA hematology test (IE). The size of the study sample was 98, and the tests were carried out in the laboratory; in which the following results were obtained: 36 positive tests, equivalent to 36.7%, 55 negative tests, equivalent to 56.1%, and 7 doubtful tests, equivalent to 7.1%; yielding a total prevalence rate of 36.7%. Regarding the results by sex: 16 females were positive, equivalent to 16.3%, and 20 males, equivalent to 20.4%. Regarding the results by age, from 0-12 months, 11 results were positive, equivalent to 11.2%; from 1-5 years old, 15 were positive, equivalent to 15.3%; and older than 5 years old, 10 were positive, equivalent to 10.2%. Regarding the results by breed: French poodle with 4 positive results, equivalent to 4.1%; mixed breed, with 21 positive results, equivalent to 21.4%; Neapolitan Mastiff, with 4 positive results, equivalent to 4.1%; German Shepherd, with 1 positive result, equivalent to 1.02%; Pit Bull, with 3 positive results, equivalent to 3.1%; Schnauzer, with 2 positive results, equivalent to 2.04%; and finally, Shar Pei, with 2 positive results, equivalent to 2.04%. The results obtained were socialized with the domestic canines’ owners living in the San Felipe neighborhood. Subsequently, an instruction manual on management, control, hygiene and prevention of toxoplasmosis in the domestic canine (canis familiaris) was delivered.